The relation between budget deficits and growth: Complicated but clear - L. Randall Wray; Eric Lin (Levy Economics Institute of Bard College, 2024)
This paper looks at the relationship between government budget deficits and the growth rate of GDP. While orthodox economic theory offers several reasons to believe that growing deficits might be associated with slower growth, and would ultimately be unsustainable, Keynesians assert that deficits could stimulate growth - at least in the short run - implying the relation between deficits and growth could be positive. Modern Money Theory, adopting Godley's sectoral balance approach, Lerner's functional finance approach, and Minsky's theory of financial instability takes a more nuanced approach. Historical data for a number of countries is presented, showing that there is no obvious relation between the deficit ratio and economic growth over long time periods. However, there is a predictable path of the relationship over the course of the business cycle for all countries examined.
Keywords: B22; B25; B52; E12; E32; E62; F43; H62; H63; 330; government budget deficit; deficit ratio; GDP growth rate; MMT; sectoral balance; functional finance; Wray curve; automatic stabilizer; Godley; Lerner